Responsiveness of B cells is regulated by the hinge region of IgD - Uebelhart, Rudolf; Hug, Eva; Bach, Martina P.; Wossning, Thomas; Duehren-Von Minden, Marcus; Horn, Anselm; Tsiantoulas, Dimitrios; Kometani, Kohei; Kurosaki, Tomohiro; Binder, Christoph J.; Sticht, Heinrich; Nitschke, Lars; et al. (Nature Immunology, 2015)
Mature B cells express immunoglobulin M (IgM)- and IgD-isotype B cell antigen receptors, but the importance of IgD for B cell function has been unclear. By using a cellular in vitro system and corresponding mouse models, we found that antigens with low valence activated IgM receptors but failed to trigger IgD signaling, whereas polyvalent antigens activated both receptor types. Investigations of the molecular mechanism showed that deletion of the IgD-specific hinge region rendered IgD responsive to monovalent antigen, whereas transferring the hinge to IgM resulted in responsiveness only to polyvalent antigen. Our data suggest that the increased IgD/IgM ratio on conventional B-2 cells is important for preferential immune responses to antigens in immune complexes, and that the increased IgM expression on B-1 cells is essential for B-1 cell homeostasis and function.
EVALuna2:26294